2011
DOI: 10.1007/s00213-011-2353-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of d-cycloserine and valproic acid on the extinction of reinstated fear-conditioned responses and habituation of fear conditioning in healthy humans: a randomized controlled trial

Abstract: A single dose of DCS or VPA might enhance exposure-based cognitive therapy of anxiety disorders by reducing the vulnerability to reinstatement and preventing relapses of fear-conditioned responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…1A and B). For subjects in the DCS and VPA groups, 100 mg DCS or 400 mg VPA was administered on an empty stomach once at 1.5 h before (Pre-treatment groups) or immediately after (Post-treatment groups) the second learning session as in our previous study (Kuriyama et al, 2011a), and 500 mg lactose was administered to subjects once at the other time point (Fig. 1B).…”
Section: Group Allocationmentioning
confidence: 97%
See 2 more Smart Citations
“…1A and B). For subjects in the DCS and VPA groups, 100 mg DCS or 400 mg VPA was administered on an empty stomach once at 1.5 h before (Pre-treatment groups) or immediately after (Post-treatment groups) the second learning session as in our previous study (Kuriyama et al, 2011a), and 500 mg lactose was administered to subjects once at the other time point (Fig. 1B).…”
Section: Group Allocationmentioning
confidence: 97%
“…A previous study suggested that both DCS and VPA enhance extinction learning of human fear conditioning and simultaneously prevent new acquisition of fear conditioning through so-called "habituation learning" (Kuriyama et al, 2011a). Although DCS exhibited a similar effect on reinstatement in rats (Ledgerwood et al, 2004), the effects of DCS and VPA on extinction and habituation learning were robust when reinstatement stimuli were exposed, rather than during the extinction and habituation learning per se, in humans (Guastella et al, 2007;Kuriyama et al, 2011a).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, the long-term retention of fear extinction is enhanced by DCS only when within-session extinction occurs (Weber et al 2007), suggesting that DCS facilitates the learning underlying extinction, rather than reducing levels of state anxiety (see Richardson et al 2004;Vervliet 2008). DCS reduces some forms of relapse, such as reinstatement, in both rats Bertotto et al 2006) and humans (Kuriyama et al 2011) but does not prevent renewal (Woods and Bouton 2006;Bouton et al 2008). A further benefit is that DCS produces a "generalization of extinction" whereby DCS-treated rats display less fear to a second CS previously paired with the same US but not extinguished (Ledgerwood et al 2005).…”
mentioning
confidence: 99%
“…One study (Kuriyama et al 2011) out of 3 found DCS (and valproic acid) to enhance extinction. This study was the only one to utilize a reinstatement component, with DCS during extinction training affecting not within-session learning or recall, but instead suppressing reinstatement.…”
Section: Pharmacological Approaches For Fear Extinction In Ptsdmentioning
confidence: 99%